Development of pH sensitive polymeric nanoparticles of erythromycin stearate - Sulekha Bhadra; Atin B Prajapati; Dipankar Bhadra (Wolters Kluwer Medknow Publications, 2016)
Context: Bioavailability of conventional tablet of erythromycin stearate is low as it is unstable at acidic pH and also shows a low dissolution rate. Objective: It was proposed to protect it from the acidic condition of the stomach along with an increase in dissolution rate by formulating pH sensitive nanoparticles. Materials and Methods: The nanoparticles were prepared by the solvent evaporation technique using different quantities of Eudragit L100-55 and polyvinyl alcohol (PVA). Size reduction was achieved by high speed homogenization technique using Digital Ultra Turrax homogenizer. The formulation was optimized using 32 factorial design, keeping drug polymer ratio and surfactant concentration as independent variables. Particle size, entrapment efficiency, and drug-release (DR) were studied as dependent variables. Results: Optimized batch containing 1:0.3 erythromycin stearate: Eudragit L100-55 ratio and 1.0% PVA showed 8.24 ± 0.71% DR in pH 1.2 in 1-h and 90.38 ± 5.97% in pH 5.5 and pH 6.8 within 2-h, respectively. Discussion: The optimized batch exhibited lower release in acidic pH and faster release in higher pH compared to the marketed preparation. Conclusion: Thus the present study concludes that pH sensitive nanoparticles of erythromycin stearate increases the dissolution of the drug in intestinal pH and also protect it from acidic pH, which may help in improving the bioavailability of erythromycin.